The Secret of Scarlett Cove - Mills, Charles; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2004)
While vacationing at Chincoteague, eleven-year-old Alex runs afoul of the Navy and a vengeful proprietor of a tourist trap, all while pursuing his Pathfinder marine mammal honor badge.
Keywords: Adult Fiction